Clinical Characteristics and Outcomes of Patients With Antithyroid Drug–Related Liver Injury - Adeel Ahmad Khan (14152953) (2023)
Context Antithyroid drugs (ATDs) are the cornerstone of hyperthyroidism management. Hepatotoxicity due to ATDs can range from mild transaminase elevation to liver transplantation requirement and mortality. Objective The primary objective of the systematic review was to assess the clinical characteristics and outcomes of patients with drug induced liver injury (DILI) due to ATDs. Methods We conducted a systematic review of PUBMED, SCOPUS, and EMBASE on characteristics and outcomes of adults (>18 years) with DILI due to ATDs. We defined DILI as bilirubin ≥2.5 mg/dL or international normalized ratio >1.5 with any rise in alanine aminotransferase (ALT), aminotransferase (AST), or alkaline phosphatase (ALP), or an elevation of ALT or AST >5 times or ALP >2 times the upper limit of normal without jaundice/coagulopathy. Results The review included 100 articles describing 271 patients; 148 (70.8%) were female (N = 209). Mean age was 42.9 ± 17.2 years. Graves’ disease was the most common indication for ATDs. Carbimazole/methimazole (CBM/MMI) was the most common offending agent (55.7%). DILI pattern was hepatocellular in 41.8%, cholestatic in 41.3%, and mixed in 16.9%. Outcomes included death in 11.8%, liver transplantation in 6.4%, partial improvement in 2.2%, and complete resolution in 79.6% with a median time (IQR) to resolution of 45 (20-90) days. Patients in the propylthiouracil (PTU) group had higher initial bilirubin, initial AST, initial ALT, peak ALT, peak AST, severe and fatal DILI, liver transplantation, and mortality than CBM/MMI. Rechallenge of antithyroid medication was infrequently reported (n = 16) but was successful in 75%. Conclusion DILI due to ATDs can present with different patterns and should prompt immediate drug discontinuation. Referral to a hepatologist should be considered if severe as transplantation is sometimes required. PTU-induced DILI may have worse outcomes than CBM/MMI. Other Information Published in: Journal of the Endocrine Society License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1210/jendso/bvad133